Sex neurosteroids: Hormones made by the brain for the brain - Fester, Lars; Rune, Gabriele M. (Neuroscience Letters, 2021)
In general, hippocampal neurons are capable of synthesizing sex steroids de novo from cholesterol, since the brain is equipped with all the enzymes required for the synthesis of estradiol and testosterone, the end products of sex steroidogenesis. Regarding estradiol, its synthesis in hippocampal neurons is homeostatically controlled by Ca2+ transients and is regulated by GnRH. Locally synthesized estradiol and testosterone maintain synaptic transmission and synaptic connectivity. Remarkably, the neurosteroid estradiol is effective in females, but not in males, and vice versa dihydrotestosterone (DHT) is effective in males, but not in females. Experimentally induced inhibition of estradiol synthesis in females and DHT synthesis in males resp. results in synapse loss, impaired LTP, and downregulation of synaptic proteins. GnRH-induced increase in estradiol synthesis appears to provide a link between the hypothalamus and the hippocampus, which may underlie estrous cyclicity of spine density in the female hippocampus. Hippocampal neurons are sex-dependently differentiated with respect to the responsiveness of hippocampal neurons to sex neurosteroids.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Hippocampus; LTP; Sex steroids; Sex-specificity; Synaptic plasticity